BIOREMEDIATION OF THE HELIOPOLIS-GUELMA GRAVEL QUARRY: A PROPOSAL FOR ENHANCING VEGETATION COVER AND ENVIRONMENTAL BENEFITS (Nigerian Journal of Technology, 2025)
Our research aims to assess the feasibility of restoring the Heliopolis quarry in Guelma, Algeria. The site has suffered degradation due to overexploitation and a lack of preventive measures. The project idea aims to enhance local environmental benefits and promote vegetation growth by introducing seeds of native plant species or seedlings. Modern techniques were employed to analyze the study area and assess soil characteristics. Technical maps and topographical representations generated through Geographic Information Systems (GIS) were created to depict the various elevation levels of the site and the degree of structural damage. Moreover, soil samples from the Heliopolis quarry and a rehabilitated quarry in Oued El Aneb, Annaba province, were analyzed using SEM-EDX. This fascinating device employs a highly focused scanning (primary) electron beam to produce high-resolution, depth-of-field images of surface topography. We applied this method to identify key elements that should be incorporated into the soil composition to improve soil fertility and facilitate effective site bioremediation. The SEM-EDX analysis results revealed varying compositions of the Heliopolis gravel quarry soil, including calcium oxide (CaO), silicon dioxide (SiO2), magnesium (Mg), and other elements in different proportions. In contrast, the soil analysis from the Oued El Aneb gravel quarry, which underwent rehabilitation in Annaba, indicated that it was enriched with all essential elements for olive tree cultivation, such as Silicon, Iron, and Magnesium. Concerning the GIS cards, the results have indicated that the quarry floor has experienced huge topographical changes, posing a substantial challenge for bioremediation due to depths exceeding 12 meters at the bottom and reaching 15 meters in some areas. The bioremediation project of the Heliopolis gravel quarry will serve the environment, provide social and economic advantages, create jobs, and enhance the overall appearance of the quarry site and the Heliopolis town.